Revisiting regimens from a philosophical perspective - Nguyen, Phu Loc; Huynh, Ngoc Trung Dung; Huynh , Loi (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Many regimen trends that aim to protect and enhance health, improve the body, and control chronic diseases have been introduced and developed in Vietnam. Especially after the COVID-19 pandemic, people care more about their health, but the expansion of regimen trends started many discussions and misunderstandings. This article reanalyzed three classic books, “Dao De Jing”, “Nan Hua Jing,” and “Huang Di Nei Jing,” based on recent achievements in science and modern medicine to strengthen the basis of regimens based on the perspectives of Taoism and Traditional Medicine. The objectives are to determine the core values and notices in regimen practices. Within the example of Oshawa’s macrobiotics, the article aims to remind regimen practitioners not to follow them without comprehension and re-equalization.